Innovative tailored fiber placement technique for enhanced damage resistance in notched composite laminate. (February 2015) - Koricho, Ermias G.; Khomenko, Anton; Fristedt, Tommy; Haq, Mahmoodul
Abstract: Composites have recently gained considerable acceptance in the transportation sector such as the aerospace and automotive industries, as these materials offer the ability to reduce weight, greenhouse gas emissions and associated fuel cost. Conversely, problems related to material behavior, cost, manufacturing process, assembly and choice of joining technique pose challenges that limit the wide acceptance and implementation of the composite materials. Specifically, a major problem related to joining is the use of mechanical/fastener joints with drilled holes that can damage the continuous fibers and cause considerable reduction in the load carrying capacity of resulting composite structures. To address this issue, an innovative solution that manufactures fabric laminates using 'tailored placement' of fibers around the holes/notch was proposed. This eliminates the need for drilling and machining of holes thereby eliminating the sources of delamination. The tensile performance of notched composites from the novel tailored fiber placement (TFP) approach was compared to conventional notched composites. Additionally, the effect of various fiber placement patterns and machining processes on the strength, damage initiation and fracture mode of notched composite laminates were studied. Specifically, the stress and strain fields around the notch were thoroughly evaluated. The experimental results for notched specimens were compared with the damage initiation and strength predictions obtained from the Hashin failure criteria as available in commercially available FEA package (ABAQUS®). A good agreement between experimental results and numerical predictions was observed. Overall, the proposed approach shows great promise in the use of tailored fiber placement technique to eliminate delaminations, maintain continuous fiber alignments and reduce associated stress concentrations in a wide range of composite applications including but not limited to mechanical fastening.